The Relationship Between Leukopenia and Dengue Fever in Child Patients - Ida Bagus Eka Utama Wija; Audrey Gunawan; Nia Reviani (International Journal of Health Engineering and Technology, 2025)
This study aims to analyze the relationship between leukocyte counts and the incidence of dengue infection in pediatric patients. The study employed a cross-sectional analytical design, collecting data from medical records of patients diagnosed with dengue fever and dengue hemorrhagic fever at RSU UKI from August 1 to 14, 2024. Among 95 patients who met the inclusion criteria, results showed that the majority experienced leukopenia, with percentages of 54.7% on the first day, 52.6% on the second day, and 44.2% on the third day. A significant relationship was found between leukocyte counts and hematocrit values (p = 0.000). Dengue fever occurred more frequently than dengue hemorrhagic fever, with higher prevalence among male patients and those aged 10–18 years. The peak of leukopenia was observed on the second day, which may help predict the critical phase of plasma leakage. Furthermore, the study highlights that monitoring leukocyte trends provides an early indicator for clinicians to anticipate disease progression and potential complications. Regular hematological evaluation, especially within the first three days of fever onset, is essential for distinguishing between mild and severe forms of dengue. The findings also support the integration of leukocyte monitoring with other clinical parameters, such as platelet count and hematocrit levels, to improve diagnostic accuracy and treatment outcomes. Early recognition of leukopenia patterns can aid in timely interventions, reducing the risk of shock and hemorrhagic manifestations. Therefore, this research reinforces the importance of leukocyte count as a vital prognostic marker in pediatric dengue cases, contributing to better patient management and clinical decision-making in endemic regions